INTERNATIONAL PRINCIPLES OF EFFECTIVE AND EFFICIENT SYSTEM OF STATE REGULATION OF FOOD SAFETY - Прилипко, Татьяна; Руснак, Леся; Букалова, Наталья (SWorldJournal, 2024)
Ukraine is rich in natural resources, which creates reliable foundations for the development of the potential of the agricultural sector. However, despite the availability of resources, the production indicators of this industry remain quite low. Currentl